*Email:fahmibeg@yahoo.com 2131 The Accuracy of Prediction for the Models IRI- 2012 and VOACAP in Measurements foF2 Over Iraq during High Solar Activity Level - Mohammed , Fahmi A. (Iraqi Journal of Science, 2022)
The accuracy of IRI- 2012 and VOACAP models during high solar activity level have been tested to know which of them is more accurate in predicting hourly foF2 values for three Iraqi cities (Baghdad, Mosul and Basrah). The results indicated that the accuracy of them increases for all hours during Spring and Summer and decreases during Winter and Autumn especially at hours near to sunrise; i.e., both of two models have the same accuracy. And that the foF2 values predicted by VOACAP model are higher than that predicted by IRI- 2012 model for all seasons.